2011
DOI: 10.1002/pbc.22936
|View full text |Cite
|
Sign up to set email alerts
|

A cost effectiveness analysis of thiopurine methyltransferase testing for guiding 6‐mercaptopurine dosing in children with acute lymphoblastic leukemia

Abstract: The present analysis suggests that screening for TPMT mutations using either genotype or enzymatic laboratory tests prior to the administration of 6-MP in pediatric ALL patients is not cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…Genotype-directed dosing schedules compared favorably with other dosing schedules, with pretreatment genotyping costing $579 per life-year saved for a 30-year-old and $1364 per life-year saved for a 60-year-old [75]. Incremental costs per child (95% confidence interval) were $277 and $298 for the genotyping and phenotyping strategies, respectively, compared to weight-based dosing [81]. However, a recent cost-effectiveness analysis in children with acute lymphoblastic leukemia (ALL) reported that screening for TPMT mutations using either genotype or enzymatic laboratory tests prior to administration of 6-MP in pediatric ALL patients did not demonstrate any survival benefit and was therefore not cost-effective.…”
Section: Cost-effectivenessmentioning
confidence: 98%
“…Genotype-directed dosing schedules compared favorably with other dosing schedules, with pretreatment genotyping costing $579 per life-year saved for a 30-year-old and $1364 per life-year saved for a 60-year-old [75]. Incremental costs per child (95% confidence interval) were $277 and $298 for the genotyping and phenotyping strategies, respectively, compared to weight-based dosing [81]. However, a recent cost-effectiveness analysis in children with acute lymphoblastic leukemia (ALL) reported that screening for TPMT mutations using either genotype or enzymatic laboratory tests prior to administration of 6-MP in pediatric ALL patients did not demonstrate any survival benefit and was therefore not cost-effective.…”
Section: Cost-effectivenessmentioning
confidence: 98%
“…Several gene/drug examples have been described for decades, 1 with various degrees of implementation across oncology institutions and practices. [42][43][44] We used a previously published method 19 to critically assess the vast number of germline pharmacogenomic studies about oncology drugs. It is noteworthy that the majority of drugs have had positive pharmacogenomic associations described about them (67 of the 125 drugs), with published associations for 12 drugs withstanding rigorous evidence standards required for clinical actionability.…”
Section: Discussionmentioning
confidence: 99%
“…This label change applied to pediatric cases since the pharmacogenetics of thiopurine in children has been directly studied [76][77][78]. Routine testing of TPMT activity prior to administration of azathioprine has been suggested to decrease deaths from neutropenic sepsis and improve quality of life [79]; however, routine testing at diagnosis in pediatric ALL has been controversial and considered by some to be non-cost-effective [80], as testing can be done later in patients with unexpectedly severe myelosuppression and adjustments made at that stage.…”
Section: Pharmacogeneticsmentioning
confidence: 99%